Penilaian Risiko Keterlambatan Pekerjaan Reparasi Kapal Bg. APC XVIII di PT. Gapura Shipyard - Akhmad Miftahul Huda; Minto Basuki (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
. In the shipbuilding industry, the repair process is a series of jobs that require a relatively short time. Delays in repairs can occur due to weak management and also caused by less than optimal empowerment of human resources. This study aims to identify the risks found in four divisions, namely the Production Division, Warehouse Division, Finance Division and Purchasing Division. The study found 31 risk events. Determining the value of each risk is carried out using the Failure Mode and Effect Analysis method. There were 13 risks that had the highest Risk Priority Number, namely the length of approval for requests for goods (RPN = 522.88), delays in payment processes by customers (RPN = 504.64), requests for additional work from the owner (RPN = 477.128), fluctuations in the number of manpower (RPN = 454.08), Changes in material use related to the availability of materials in the warehouse (RPN = 411.768), Changes in material calculations related to design (RPN = 389.017), Length of decision making by the owner (RPN = 388.36), Long material delivery process (RPN = 388.36), Insufficient stock material (RPN = 357,588), Writing the amount on the Request for Goods Bill is not detailed (RPN = 357.71), Lack of availability of stock material (RPN = 349,524), Making and submitting late payment requests (RPN = 316.8), Placement of materials that are less efficient (RPN = 296.8) Risk mitigation is carried out using the Fault Tree Analysis method to find the main cause / basic event of each risk. And the mitigation step that needs to be done is by making changes to the warehouse layout. If the layout design of the warehouse is changed to be more efficient it will speed up the material retrieval process which has an impact on the ship repair process time.